FUNGSI NYANYIAN SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN PENGUASAAN KOSAKATA ANAK USIA 4-5 TAHUN DI TK - Yuliati Yuliati; Fadillah Fadillah; Aloysius Mering (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractResearch on the function of this song was conducted to explain the singing function as a learning medium to improve the mastery of vocabulary for children aged 4-5 years in TK ‘Aisyiyah, Bengkayang Regency, after singing learning. This study uses a qualitative approach with classroom action research methods with data retrieval using instruments. The researcher directly observes and then takes the actions carried out by the researcher himself. This classroom action research is conducted in 2 (two) cycles, each cycle consisting of 2 meetings. The song used was created by researchers for research purposes. The two songs are themed about me and my body, with different sub-themes, namely sub-themes about body members with Body song titles, and favorite color sub-themes with Color song titles. The results of this study can be concluded to be successful because of the increase in vocabulary mastery through singing activities up to 92% in children aged 4-5 years in kindergarten ‘Aisyiyah Bengkayang district after learning through singing and the changing atmosphere of learning becomes more active, creative, effective and fun. Keywords: Function of song, Kindergarten, Learning media, Vocabulary mastery